2016
DOI: 10.1038/oncsis.2016.74
|View full text |Cite
|
Sign up to set email alerts
|

The HIF/PHF8/AR axis promotes prostate cancer progression

Abstract: Recent studies provide strong evidence that the androgen receptor (AR) signaling pathway remains active in castration-resistant prostate cancer (CRPC). However, the underlying mechanisms are not well understood. In this study, we demonstrate that plant homeo domain finger protein 8 (PHF8 )interacts with and functions as an essential histone demethylase activity-dependent AR coactivator. Furthermore, we demonstrate that the expression of PHF8 is induced by hypoxia in various prostate cancer cell lines. Knockdow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 42 publications
3
38
1
1
Order By: Relevance
“…2A and B). This is consistent with the published data on the upregulation of PHF8 protein [17,18], but not RNA level [17]. We also found that ENO2 was strongly upregulated at later time points (Supplementary Fig.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…2A and B). This is consistent with the published data on the upregulation of PHF8 protein [17,18], but not RNA level [17]. We also found that ENO2 was strongly upregulated at later time points (Supplementary Fig.…”
Section: Resultssupporting
confidence: 93%
“…However, the c-MYC-miR-22-PHF8 axis is decoupled under hypoxia (1% O 2 , 6 day treatment), with c-MYC downregulated but PHF8 post-transcriptionally upregulated. Recently, it was reported that in the context of hypoxia HIF1α and HIF2α transcriptionally upregulate PHF8, which interacts with AR and enhances its transcriptional activity [18]. In the current study, we report PHF8 plays a critical role in hypoxia signaling as it: positively regulates KDM3A which is a critical coactivator of HIF1α; indirectly sustains H3K4me3 levels on select hypoxia-inducible genes; and is required for full activation of HIF1α through various mechanisms.…”
Section: Introductionsupporting
confidence: 52%
See 3 more Smart Citations